Penggunaan Model Pembelajaran STEM di Sekolah Dasar dalam Pembelajaran IPA - Nur Faizah; Dwi Septiana; Risma Yulianty (Indonesian Publication Center, 2022)
This research is a qualitative type. The purpose of this study was to determine the needs of elementary school teachers in studying the use of the STEM learning model. This study used to interview and observation techniques for elementary school teachers. This study also uses a literature review technique. The qualitative method was chosen because it has relevant results. From the results of the interviews, it was found that the teacher had used the STEM learning model. The results of the interviews and observations showed that learning using the STEM learning model was good for use in elementary schools. The advantage of learning using the STEM model is that students are more active and interactive. Students are also more familiar with current technological developments such as learning to use PPT and projectors and the application of scientific trials.